Regulation of fibroblast migration by tenascin-C. (20th July 2007) - Trebaul, A.; Chan, E.K.; Midwood, K.S.
Abstract : Synthesis of new tissue by fibroblasts is required for tissue rebuilding in response to injury. Fibroblast migration from surrounding healthy tissue into the fibrin–fibronectin provisional matrix deposited upon injury is a key rate-limiting step of this stage of tissue repair. These events must be tightly regulated. Excessive deposition of scar tissue is the major hallmark of fibrotic disease. Tenascin-C is an extracellular matrix glycoprotein that is transiently expressed upon tissue injury, where it is specifically localized to the wound edge, and persistently up-regulated in fibrotic disease. We have shown that full-length tenascin-C promotes fibroblast migration within fibrin–fibronectin matrices and we have mapped the domains within the molecule critical for enhancing migration. We also demonstrated that specific fragments of tenascin-C inhibit fibroblast migration. These results suggest that transient expression of tenascin-C at the wound boundary is key to tissue repair: its induction recruits fibroblasts into the wound and fragments resulting from its breakdown prevent excessive fibroblast infiltration. Our results demonstrate how fibroblast migration in three-dimensional provisional matrices may be differentially regulated by proteolysis of matrix molecules and could explain how persistent expression of tenascin-C contributes to the progression of fibrotic disease.